The Effects Of Planting Distance Treatment And Zeolite Application As Ameliorants On Growth And Yield Of Bok Choy Plants - Mario Donald Bani; Gregorio Antonny Bani (Jurnal Informasi, Sains dan Teknologi, 2023)
The increasing market demand for Bok choy makes the need to apply a good cultivation system for the optimum growth and productivity of the plants very important. One of the main factors that must be considered in cultivating Bok choy is the treatment of plant spacing in which the soil is often enriched with ameliorants, such as zeolite. The combination treatment of plant spacing and zeolite showed a significant effect on the growth and productivity of Bok choy plants, where the further the plant spacing, the higher the growth rate. However, the same plant spacing treatment did not affect the pH value. The best zeolite treatment was 150 g/1x5 m2 soil bed, or 300 kg/ha.